Knockdown of Amyloid Precursor Protein: Biological Consequences and Clinical Opportunities - Gabriele, Rebecca M. C.; Abel, Emily; Fox, Nick C.; Wray, Selina; Arber, Charles (Frontiers in Neuroscience, 2022)
Amyloid precursor protein (APP) and its cleavage fragment Amyloid-β (Aβ) have fundamental roles in Alzheimer’s disease (AD). Genetic alterations that either increase the overall dosage of APP or alter its processing to favour the generation of longer, more aggregation prone A species, are directly causative of the disease. People living with one copy of APP are asymptomatic and reducing APP has been shown to lower the relative production of aggregation-prone A species in vitro. For these reasons, reducing APP expression is an attractive approach for AD treatment and prevention. In this review, we will describe the structure and the known functions of APP and go on to discuss the biological consequences of APP knockdown and knockout in model systems. We highlight progress in therapeutic strategies to reverse AD pathology via reducing APP expression. We conclude that new technologies that reduce the dosage of APP expression may allow disease modification and slow clinical progression, delaying or even preventing onset.